2004
DOI: 10.1186/1475-2883-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundLittle information is available on methods of treatment practiced by patients affected by filarial lymphoedema in Sri Lanka. The frequency and duration of acute dematolymphangioadenitis (ADLA) attacks in these patients remain unclear. This study reports the knowledge, practices and perceptions regarding lymphoedema management and the burden of ADLA attacks among patients with lymphoedema.MethodsA semi-structured questionnaire was used to assess morbidity alleviation knowledge, practices and perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…The lymphoedema patients reported cleaning the affected limbs once a day which is comparable to studies in India [37,38]. The majority of lymphoedema patients do not inspect entry lesions, elevate the affected limb, exercise, and use the appropriate footwear on the affected (inappropriate practices for lymphoedema management) which was in contrast to the findings of other studies [38][39][40]. The difference might be due to the lack of training/health education given to the lymphoedema patients and in the community on the management of filarial lymphoedema and they were not followed up [41].…”
Section: Discussionsupporting
confidence: 61%
“…The lymphoedema patients reported cleaning the affected limbs once a day which is comparable to studies in India [37,38]. The majority of lymphoedema patients do not inspect entry lesions, elevate the affected limb, exercise, and use the appropriate footwear on the affected (inappropriate practices for lymphoedema management) which was in contrast to the findings of other studies [38][39][40]. The difference might be due to the lack of training/health education given to the lymphoedema patients and in the community on the management of filarial lymphoedema and they were not followed up [41].…”
Section: Discussionsupporting
confidence: 61%
“…Published studies done among clinic attendees on lymphoedema management knowledge and practices, summarized below, provided evidence on the important role played by these clinics in morbidity management [ 22 , 23 ]. Filariasis clinic attendees surveyed over a decade ago in the districts of Colombo and Gampaha revealed that the majority washed their limbs on a daily basis with soap and water (Colombo 75.5% and Gampaha 89.4%) while around half of the population practiced limb elevation (Colombo 46.6% and Gampaha 50%) and only a minority practiced recommended limb exercises (Colombo 14.7% and Gampaha 6%) [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, cultural factors may restrict women’s activities to domestic ones, which differ from farming and other occupations that men might have in the same culture; these differences could lead to different productivity losses. [ 44 , 46 , 48 , 96 , 107 ] Second, when performing the same tasks, women can perform differently from men. [ 64 ] Third, the same sequela can affect men and women differently.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on lymphatic filariasis have shown that the expenditures of patients seeking treatment due to LF sequelae are not negligible, even after they are treated with anti-parasitic drugs. [ 40 , 43 , 44 , 46 , 47 , 52 , 75 83 ] Therefore, we calculated the direct costs arising from lymphedema and hydrocele. Annual out-of-pocket payment costs were calculated for each WHO region separately since treatment type and costs can vary between regions.…”
Section: Methodsmentioning
confidence: 99%